Study on the acceptance of Malaysia citizen on PRIMA 1 Malaysia housing scheme - Nur Sheila, Mohamad (2018)
Every family in Malaysia dream of owning a house as a shelter. Their dream depends on their household monthly income that qualify them to make a bank loan. Due to pricy house price now days, many still could not afford to purchase a house. A project called PRIMA 1 Malaysia housing scheme by Malaysian government has been introduce to plan, built, construct and offer high-quality housing conceptualizing a modern lifestyle for middle-income city residents. PRIMA has come with a list of house price including its facilities and a financing plan which is stepped up end financing scheme. Therefore this study is carried out to identify the buying behavior of PRIMA 1 Malaysia buyer and to propose suitable method to meet the needs of the potential buyers. A set of questionnaire was made by Google form which contain question about the major factor of acceptance of Malaysian citizen on PRIMA house 1 Malaysia. The total of 480 questionnaire was distributed and only 205 were returned answered which give a value of 43%. The data collected from the questionnaire distributed was analyzed by using “Average Index” (AI). The degree of importance in this study was determined by the rating scales. From the study, people acceptance on PRIMA house is high based on its price, facilities and services and their finances. It was found that the buyer’s finance is very important for their acceptance and perception on PRIMA 1 Malaysia Housing Scheme, government can come with a lower interest package for about first 5 years to reduce the tax price of PRIMA house. Other than that, it was also found that, PRIMA services to people are also crucial for people acceptance and perception on PRIMA 1 Malaysia Housing Scheme. To increase the efficiency of PRIMA, government can reduce the bureaucracy system to make PRIMA more efficient.